Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.5694/j.1326-5377.2009.tb02276.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with skin disease and their relationships with their doctors: a qualitative study of patients with acne, psoriasis and eczema

Abstract: Objective: To explore the experiences of patients with acne, psoriasis or atopic eczema in their relationships with their treating doctors. Design: Qualitative study, using semi‐structured interviews conducted between January 2004 and April 2005, thematic analysis and modified grounded theory methodology. Setting and participants: Participants were patients with acne, psoriasis or atopic eczema recruited from urban general practices and urban dermatology practices. Results: 62 semi‐structured interviews were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 22 publications
4
58
0
1
Order By: Relevance
“…Previous studies have shown that acne is associated with significant morbidity and decrease in health-related quality of life. Both general practitioners and dermatologists were reported as having poor comprehension of the psychological implications of skin diseases, being insensitive to their patients' emotional suffering, and trivialising participants' disease [18]. In this study the degree of acne-related quality of life changes on patients were studied in relation to acne severity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that acne is associated with significant morbidity and decrease in health-related quality of life. Both general practitioners and dermatologists were reported as having poor comprehension of the psychological implications of skin diseases, being insensitive to their patients' emotional suffering, and trivialising participants' disease [18]. In this study the degree of acne-related quality of life changes on patients were studied in relation to acne severity.…”
Section: Resultsmentioning
confidence: 99%
“…The context of this statement is that skin diseases may be associated with significant psychological morbidity 4–6 . Furthermore, it has been demonstrated that in many dermatological conditions, dermatologists underestimate the prevalence of psychiatric morbidity 7,8 and that a mismatch of patients’ and doctors’ perceptions of the seriousness of their illness causes patients’ distress and impairs the doctor–patient relationship 9 . The level of congruence of doctors’ assessments of patients’ skin disease severity is of considerable clinical importance as even objectively mild skin disease may precipitate significant psychological morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…'s research). Often adopting a qualitative approach, these studies explore the day‐to‐day barriers and enablers that people experience in self‐managing conditions, using health services and/or pursuing healthy behaviours as well as how the array of options available in a person's social context shapes their health decision‐making and outcomes . Aligned with this, Gilhooley et al .…”
mentioning
confidence: 99%